Analisis Drug Related Problems dan Pengaruhnya terhadap Pengendalian Glukosa Darah pada Pasien Covid-19 dengan Komorbiditas Diabetes Melitus Tipe 2 - Yoppy Mayrosa; Hesty Utami Ramadaniati; Dian Ratih Laksmitawati; Ivans Panduwiguna (Syntax Corporation, 2023)
This study aims to anayze the effect of drug related problems (DRPs) on glycemic control in COVID-19 patients with comorbid diabetes mellitus type 2. This research is a cross-sectiona study using retrospective data obtained from secondary data from the medica records of Covid-19 patients. with type 2 diabetes mellitus. The research location was at Jati Padang Hospita. The sample consisted of 76 medica records with total sampling method. Data collected using PCNE V9.00 were then tested using the Wilcoxon test comparing initia GDS in hospita with GDS at the end of patient discharge, the Chisquare test which correlated changes in GDS with patient clinica outcomes and the Spearman test which linked changes in GDS with DRPs, characteristics of Covid-19 patients with diabetes mellitus predominant age 46-55 years (30.3%), predominant sex mae (51.3%), length of stay 6-10 days (64.5%), profile of drug use that is often used antivira, antibiotics, vitamins and supplements, symptomatic and antidiabetic (100%). The most common comorbidities were hypertension (60.4%), the incidence of DRPs (92.1%), the most common fina GDS was hyperglycemia (â‰¥ 200 mg/dL) (65.8%). 58 patients were discharged with a negative sample (76.3%). The results of the Wilcoxon test on blood glucose showed differences in blood glucose at the beginning and at the end. The results of the Chi-square test between changes in blood glucose and the patient's clinica outcome (p>0.05) showed that there was no significant relationship between changes in blood glucose levels and the patient's clinica outcome. Spearmen's correlation test results (p>0.05) showed a significant relationship between DRPs and changes in patient's blood glucose. The correlation between the incidence of DRPS and blood glucose (0.169) shows a weak relationship. It can be interpreted that DRPs do not realy affect changes in blood glucose in patients at Jati Padang Hospital.